A high throughput device for label-free real-time study of cellular secretion with iSCAT microscopy - Gemeinhardt, Andre; König, Katharina; Dahmardeh, Mahyar; Sandoghdar, Vahid (Optics InfoBase Conference Papers, 2020)
We use interferometric scattering microscopy (iSCAT) to study in-situ secretion dynamics of living cells. The method allows us to optically detect single proteins in real-time without the need for labeling.
CRIS-Team Scopus Importer:2020-10-02